2019
DOI: 10.1021/jacs.8b09306
|View full text |Cite
|
Sign up to set email alerts
|

Direct Identification of Active Surface Species for the Water–Gas Shift Reaction on a Gold–Ceria Catalyst

Abstract: The crucial role of the metal–oxide interface in the catalysts of the water–gas shift (WGS) reaction has been recognized, while the precise illustration of the intrinsic reaction at the interfacial site has scarcely been presented. Here, two kinds of gold–ceria catalysts with totally distinct gold species, <2 nm clusters and 3 to 4 nm particles, were synthesized as catalysts for the WGS reaction. We found that the gold cluster catalyst exhibited a superiority in reactivity compared to gold nanoparticles. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
142
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(158 citation statements)
references
References 44 publications
7
142
0
Order By: Relevance
“…Fu et al synthesized two different kinds of Au/Ce WGS reaction catalysts supported on the same nanorods of ceria, one with < 2 nm disordered clusters, and the other with 3-4-nm particles. The results exhibited that the disordered gold clusters had superior activity than the nanoparticles of gold [60]. Stere et al utilized nonthermal (cold) plasma activation to facilitate low-temperature WGS reaction over an Au-based/CeZrO 4 catalyst, where they concluded that the catalyst activity was comparable to that achieved through heating the catalyst up to 180°C [61].…”
Section: Noble Metal Basedmentioning
confidence: 99%
“…Fu et al synthesized two different kinds of Au/Ce WGS reaction catalysts supported on the same nanorods of ceria, one with < 2 nm disordered clusters, and the other with 3-4-nm particles. The results exhibited that the disordered gold clusters had superior activity than the nanoparticles of gold [60]. Stere et al utilized nonthermal (cold) plasma activation to facilitate low-temperature WGS reaction over an Au-based/CeZrO 4 catalyst, where they concluded that the catalyst activity was comparable to that achieved through heating the catalyst up to 180°C [61].…”
Section: Noble Metal Basedmentioning
confidence: 99%
“…In the associative mechanism, CO and H 2 O adsorb on the catalyst to form an intermediate, which decomposes to yield CO 2 and H 2 . It has been proved that with associative mechanism, surface hydroxyl serves as the active species in Au/CeO 2 system 49,50 . In this case, two CO molecules react with two surface hydroxyl groups to form 2 CO 2 molecules and 1 H 2 molecule:…”
Section: Resultsmentioning
confidence: 99%
“…These observations matched the features of redox mechanism, assuming that H 2 O dissociated on CeO 2 oxygen vacancy to generate H 2 and active surface oxygen atoms. After H 2 O injection, we removed the surface oxygen with H 2 reduction and preserved the surface hydroxyls 50 , after which CO was purged into the system to conduct the TPSR test again. The subsequent CO treatment gave a CO 2 :H 2 ratio of 2:1, showing the typical results of associative mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the catalytic behavior of SACs shall be significantly tailored by the presence of the OH groups. Moreover, since the catalytic performance of the WGS reaction is directly related to the interfacial atoms of the catalysts, which is maximized at the single atom limit, it is significant and highly desirable to develop SACs with high concentration of isolated NM atoms anchored on the oxide support for maximizing the catalytic activity of WGS reaction.…”
Section: Applicationsmentioning
confidence: 99%